Pengembangan Media Pembelajaran Interaktif Articulate Storyline Berbasis Literasi Digital Pada Pembelajaran IPS bagi Siswa Madrasah Ibtidaiyah Negeri - Selsabila, Viola; Pramudiani, Puri (Jurnal Paedagogy, 2022)
This research aims to analyze the quality, feasibility, and response of educators and students to the Storyline Articulated by interactive learning media based on digital literacy. The study was conducted in the even semester academic year of 2021/2022 at the Madrasah Ibtidaiyah Negeri 12 Cibubur. This research used the ADDIE model’s research and development methods (Research and Development). Data from interviews and evaluations in the form of criticism and ideas were used in this research instrument. Meanwhile, data analysis techniques used data based on numbers such as questionnaires and validations. The validation test results by two validators, namely the media expert validator, obtained a percentage value of 72% in the interpretation into the feasible category, and the material expert validator obtained an average percentage value of 80% with a very feasible category. Educators’ response to learning media obtained a score of 90% with a very decent category. Based on the research data, interactive learning media for digital Literacy-BasedÂ Articulation StorylinesÂ in class IV social studies learning at Madrasah Ibtidaiyah Negeri 12 Cibubur is suitable for learning activities.